2021
DOI: 10.1002/jmr.2922
|View full text |Cite
|
Sign up to set email alerts
|

Vatairea guianensis lectin stimulates changes in gene expression and release of TNF‐α from rat peritoneal macrophages via glycoconjugate binding

Abstract: Using a rat model of peritonitis, we herein report the inflammatory effect induced by the lectin isolated from Vatairea guianensis (VGL) seeds in the context of interactions between VGL and both toll-like receptor 4 (TLR4) and tumor necrosis factor receptor 1 (TNFR1). Peritoneal macrophages were stimulated with VGL for dose-dependent gene expression and release of TNF-α. In vivo results showed that VGL (1 mg/kg; intraperitoneal) induced peritonitis in female Wistar rats. Leukocyte migration, macrophage activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…It is well demonstrated that lectins have been used as tools in the study of inflammatory processes as they have the capacity of reversible and specific binding to glycan structures present in the membranes of inflammatory cells [24,25,26]. In the other study, LAL presented antiinflammatory activity via lectin domain, inhibiting neutrophil migration to rat peritoneal cavity and modulating inflammatory mediators [2].…”
Section: Discussionmentioning
confidence: 98%
“…It is well demonstrated that lectins have been used as tools in the study of inflammatory processes as they have the capacity of reversible and specific binding to glycan structures present in the membranes of inflammatory cells [24,25,26]. In the other study, LAL presented antiinflammatory activity via lectin domain, inhibiting neutrophil migration to rat peritoneal cavity and modulating inflammatory mediators [2].…”
Section: Discussionmentioning
confidence: 98%
“…The characterization of these lectins allowed the division into three groups based on specificity, in particular the mannose/glucosespecific, the N-acetylgalactosamine/galactose-specific, and the N-acetylglucosamine-specific Dalbergieae lectins. Some of these proteins elicit interesting biological effects such as pro-and anti-inflammatory [6][7][8],…”
Section: Introductionmentioning
confidence: 99%
“…(Fabaceae, Papilionoideae) is a common tree in the Brazilian Amazon region, and its leaves and fruits are traditionally used for the treatment of dermatological mycosis. The plant is commonly known as “fava de impingem”, “faveira amarela”, or “faveira grande do igapó” in Brazil . Because of its floral morphology, the genus Vatairea was previously assigned to the Dalbergieae tribe, but was recently reassigned to the unranked Vataireoid clade after DNA sequence based phylogenetic analyses. , Extensive pharmacological studies were performed on Vatairea guianensis lectin (VGL), which was obtained from its seeds and exhibited vasorelaxant and anti-inflammatory effects. ,, …”
mentioning
confidence: 97%